Stress analysis in pedicle screw and bone interface by various contact models in scoliotic spine fixation. Issue 4 (April 2020) - Rusli, M; Dahlan, H; Sahputra, R E; Bur, M
Abstract: Scoliosis is a musculoskeletal condition that has an abnormal lateral spinal curvature as its main feature. By a level curvature condition, the scoliotic spine has to treat by surgery process to install an instrument or implant consists of pedicle screws, rods, and connectors in fixation of the spinal curvature. However, it is observed in many cases that several types of failure occur in the instrument and the bone - pedicle screw interface. One of the problems was related to screw loosening and pulled out from the spine. This paper observes and discusses the stress distribution numerically in the screws and bone interface in scoliotic spine fixation using finite element analysis. The contact interface is modeled variously by bonded contact and friction contact. It is found that in bonded connection between screws and bone generates lower maximum stress than friction contacts. The maximum stress is working in the screw and the stress distribution is more uniform along the contact surface. Therefore, the risk of pulling out the screws will be minimized. On the other hand, friction contact with low friction coefficients makes the stress distribution is concentrated in a specific region and increase the maximum stress in bone.